Aleurites moluccana (L.) Willd.: Ecology, silviculture and productivity - Krisnawati, H.; Kallio, M.H.; Kanninen, M. (Center for International Forestry Research, 2011)
This manual gathers information on the ecology and silviculture of Aleurites moluccana (L.) Willd., with a focus on Indonesia. It also includes growth and yield data from published sources and collected from smallholders’ farms in the research sites in South Kalimantan province. The manual is one of five manuals to guide smallholder tree planting of five selected tree species in Indonesia. The other four species are: Acacia mangium Willd.; Anthocephalus cadamba Miq.; Paraserianthes falcataria (L.) Nielsen; and Swietenia macrophylla King. Smallholders in Indonesia have planted trees on private or community land for a long time. Various actors have encouraged this activity to improve local livelihoods, environmental sustainability and industrial wood supply. These efforts have been generally successful, but they are often undertaken without technical assistance. Since farmers often lack technical capacity and management know-how, the quality and quantity of products may not be optimal. Productivity of smallholder plantations can be improved by enhancing smallholders’ management knowledge and skills, including species selection based on site matching, silvicultural management to produce high-quality products, and pest and disease management.